Surrogacy in Our Region - How Do We Help Our Patients Who Have No Other Options? - Somjate Manipalviratn (Fertility & Reproduction, 2023)
Gestational surrogacy is a well-established fertility treatment with promising treatment success. Gestational surrogacy has multiple dimensions to consider such as medical, psychological, legal, and ethical aspects. Gestational surrogacy is allowed/supported only in some countries which limit access of the couples who require treatment in many countries. Many countries have surrogacy law to regulate gestational surrogacy and to provide legal rights of the intended parents over the birth of their child from the surrogate mother. Surrogacy law also provide protection to the right of the surrogate mother as well. Surrogacy law differs from countries to countries which lead to an increasing trend of cross-border gestational surrogacy treatment toward the countries which allow legal gestational surrogacy or to the country with no law to regulate gestational surrogacy. The intended parents may face legal problems before returning to their countries of origin or when trying to have their children legally recognized in their countries. The intended parents exploring cross-border surrogacy treatment should get legal counsel in their own country to assist with immigration, parentage, and citizenship for the child born through a surrogacy arrangement outside their own country. Due to limitation to gain access to gestational surrogacy for couples in many countries, there is rapidly growing research on the uterus transplantation with reported success on giving birth to healthy children. This could be an alternative to gestational surrogacy for women with uterine factor infertility. However, this also pose some ethical challenge on the uterus donation as organ.